Department Chairs' Trends and Issues: A 10-Year study - Robert E. Cipriano Dr. (Academic Chairpersons Conference Proceedings, 2017)
I have been surveying chairs for the past 10 years in an effort to determine the challenges they face, the demonstrated skills they indicate are needed for them to be effective, characteristics of people serving in this unique leadership position, how satisfied they are, those tasks that are pleasant or unpleasant. I have been following trends over 10-years. I am able to inspect those items that remain fixed over time, and those that have changed. This presentation will provide data to inform the attendees and demystify important components of chairing a department.
Keywords: department chair; surveying chairs; retrospective analysis; trends on chairs; challenges of chair